\( 2\log_82+\log_83= \)
\( \log_812 \)
\( \log_87 \)
\( \frac{1}{2}\log_24\times\log_38+\log_39\times\log_37= \)
\( \log_3392 \)
\( \log_{15(252\sqrt{2})} \)
\( 3\log_49+8\log_4\frac{1}{3}= \)
\( 11\log_43 \)
\( -\log_49 \)
\( \log_{10}3+\log_{10}4= \)
\( \log_{10}7 \)
\( \log_{10}12 \)
\( \log_974+\log_9\frac{1}{2}= \)
\( \log_974.5 \)
\( \log_937 \)
2log82+log83= 2\log_82+\log_83= 2log82+log83=
2log82=log822=log84 2\log_82=\log_82^2=\log_84 2log82=log822=log84
2log82+log83=log84+log83= 2\log_82+\log_83=\log_84+\log_83= 2log82+log83=log84+log83=
log84⋅3=log812 \log_84\cdot3=\log_812 log84⋅3=log812
log812 \log_812 log812
12log24×log38+log39×log37= \frac{1}{2}\log_24\times\log_38+\log_39\times\log_37= 21log24×log38+log39×log37=
We break it down into parts
log24=x \log_24=x log24=x
2x=4 2^x=4 2x=4
x=2 x=2 x=2
log39=x \log_39=x log39=x
3x=9 3^x=9 3x=9
We substitute into the equation
12⋅2log38+2log37= \frac{1}{2}\cdot2\log_38+2\log_37= 21⋅2log38+2log37=
1⋅log38+2log37= 1\cdot\log_38+2\log_37= 1⋅log38+2log37=
log38+log372= \log_38+\log_37^2= log38+log372=
log38+log349= \log_38+\log_349= log38+log349=
log3(8⋅49)=log3392 \log_3\left(8\cdot49\right)=\log_3392 log3(8⋅49)=log3392x=2 x=2 x=2
log3392 \log_3392 log3392
3log49+8log413= 3\log_49+8\log_4\frac{1}{3}= 3log49+8log431=
Where:
3log49=log493=log4729 3\log_49=\log_49^3=\log_4729 3log49=log493=log4729
y
8log413=log4(13)8= 8\log_4\frac{1}{3}=\log_4\left(\frac{1}{3}\right)^8= 8log431=log4(31)8=
log4138=log416561 \log_4\frac{1}{3^8}=\log_4\frac{1}{6561} log4381=log465611
Therefore
log4729+log416561 \log_4729+\log_4\frac{1}{6561} log4729+log465611
logax+logay=logaxy \log_ax+\log_ay=\log_axy logax+logay=logaxy
(729⋅16561)=log419 \left(729\cdot\frac{1}{6561}\right)=\log_4\frac{1}{9} (729⋅65611)=log491
log49−1=−log49 \log_49^{-1}=-\log_49 log49−1=−log49
−log49 -\log_49 −log49
log103+log104= \log_{10}3+\log_{10}4= log103+log104=
log1012 \log_{10}12 log1012
log974+log912= \log_974+\log_9\frac{1}{2}= log974+log921=
log937 \log_937 log937
\( \log_24+\log_25= \)
\( \log_220 \)
\( \log_420 \)
log24+log25= \log_24+\log_25= log24+log25=
log220 \log_220 log220